Kantasaamesta eteläkantasaameen: Lainatodisteita eteläsaamen varhaisesta eriytymisestä - Piha, Minerva; Häkkinen, Jaakko (Sananjalka, 2020)
This article examines which loaning features indicate that the predecessor of South Saami – Southern Proto-Saami – drifted off from common Late Proto-Saami at an early date. We also suggest that this drift refers to linguistic immigration to central Scandinavia where South Saami is spoken today. Loanword evidence provided are those from Northwest Germanic and Proto-Scandinavian found in South Saami that either have irregular sound substitutes compared to other Saami languages (e.g. South Saami word-medial -r- in snaejrie ‘slice (of bread, cheese)’ cf. Inari Saami -tt- in snáittu ‘splint’; South Saami initial h- in haame ‘antlerless reindeer doe’ cf. North Saami ápmil); they are not found in any other Saami language (e.g. saar- in Saaraahka ‘creative old woman (divinity)’) or they have deviating semantic meaning compared to other Saami languages (South Saami duvrie ‘bear’; cf. North Saami divri ‘insect’). The number of such loanwords is 53 out of about 170. Even those loanwords, which do not show any kind of irregularity when compared to other Saami languages, may have been borrowed into South Saami separately, however they do not contain any of those sounds that started a deviating development after the drift. In absolute chronology, the initial areal and dialectal drift happened in southern Finland around 200 CE. Features presented here are so numerous, though many of them are still quite sporadic, that we find there is sufficient evidence to show the early drift of South Saami. This dating also correlates with the changes seen in archaeological data taken from the South Saami-speaking area. Thus, the changes in archaeological material most likely are caused by Saami speakers arriving to a new land and their intensively active contacts with the people already inhabiting the area.